2012
DOI: 10.1167/iovs.11-8450
|View full text |Cite
|
Sign up to set email alerts
|

Müller Cell Expression of Genes Implicated in Proliferative Vitreoretinopathy Is Influenced by Substrate Elastic Modulus

Abstract: There are significant changes in morphology, cytoskeletal integrity, and gene regulation in Müller cells as a function of the stiffness of the substrate. Changes in local tissue elastic modulus may have a role in vitreoretinal disorders. These findings also may have implications for strategies for improved integration of retinal prosthetics, and for stem cell therapies, particularly targeting the transcriptional regulators YAP and TAZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 36 publications
1
28
0
1
Order By: Relevance
“…These genes are associated with proliferative vitreoretinopathy, a well-known complication that develops after retinal detachment, and were expressed in Müller cells cultured on soft substrates designed to mimic the loss of tissue stiffness found in a detached retina. 33 In our floating cultures, the phenomenon of Müller cell activation and tissue disruption was most pronounced, indicating a direct relationship between the biomechanical milieu and explant cell survival.…”
Section: Figure 6 Immunohistochemical Labeling Of Müller Cells Usingmentioning
confidence: 71%
“…These genes are associated with proliferative vitreoretinopathy, a well-known complication that develops after retinal detachment, and were expressed in Müller cells cultured on soft substrates designed to mimic the loss of tissue stiffness found in a detached retina. 33 In our floating cultures, the phenomenon of Müller cell activation and tissue disruption was most pronounced, indicating a direct relationship between the biomechanical milieu and explant cell survival.…”
Section: Figure 6 Immunohistochemical Labeling Of Müller Cells Usingmentioning
confidence: 71%
“…AFM indentation has been successfully applied for measuring the mechanical properties of a range of cell types, 25,[34][35][36] and has been used extensively for assessing changes in mechanical properties of cells associated with cellular differentiation and in various diseased contexts. 30,37 An important step to calculate stiffness from force-curve is identifying the point where the tip first makes contact with the cell. The uncertainty in contact point can affect the elastic modulus 31 .…”
Section: Discussionmentioning
confidence: 99%
“…They found that fibroblasts actively stiffen their cytoskeletons to match the stiffness of substrates they adhere to. Many other cell types have also been reported to become stiffer when cultured on stiffer substrates 30 .…”
Section: Figure 2amentioning
confidence: 99%
“…The FNIII Domain D of TN-C is necessary to stimulate retinal outgrowth on Müller glia cells (Siddiqui et al, 2008). An increase in Müller cell proliferation has been observed on stiff substrates and an upregulation of connective tissue growth factor (CTGF) and TN-C on softer substrates (Davis et al, 2012). Recently, Müller cells were shown to have the potential to re-enter the cell cycle and differentiate into multipotent neuronal progenitors that can regenerate cells in damaged areas.…”
Section: Tenascinmentioning
confidence: 99%